Tinjauan Historis Pengungsian Vietnam di Pulau Galang 1979-1996 - Hendri, Zendri; Dandi, Rahmad (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2022)
Vietnam's long history starts from the effort to gain independence from France, the prolonged civil war between Communist North Vietnam and nationalist South Vietnam, to the Vietnamese invasion of Cambodia, which led to the massive migration of Vietnamese people to various countries using boats so that refugees This Vietnamese, known as the "Boat People." This study provides a comprehensive explanation of the background of the migration of Vietnamese refugees to Galang Island, the role of UNHCR and the Government of Indonesia in overcoming these problems, and their lives on Galang Island. This historical research was carried out successively from the heuristic process taken from the Vietnam-camp refugee document and observations on Galang Island. The data is then verified, interpreted analytically and synthetically, and presented in descriptive-explanative historiography. Apart from the pluses and minuses of various aspects of the history of Vietnamese refugees on Galang Island from 1979 to 1996, the Indonesian government has been maximal in overcoming the problem of Vietnamese refugees.